Carnosol, a Natural Polyphenol, Inhibits Migration, Metastasis, and Tumor Growth of Breast Cancer via a ROS-Dependent Proteasome Degradation of STAT3 - Alsamri, Halima (Front Oncol, 2019)
We have previously demonstrated that carnosol, a naturally occurring diterpene, inhibited in vitro cell viability and colony growth, as well as induced cell cycle arrest, autophagy and apoptosis in human triple negative breast cancer (TNBC) cells. In the present study, we evaluated the ability of carnosol to inhibit tumor growth and metastasis in vivo. We found that non-cytotoxic concentrations of carnosol inhibited the migration and invasion of MDA-MB-231 cells in wound healing and matrigel invasion assays. Furthermore, gelatin zymography, ELISA, and RT-PCR assays revealed that carnosol inhibited the activity and downregulation the expression of MMP-9. Mechanistically, we demonstrated that carnosol suppressed the activation of STAT3 signaling pathway through a ROS-dependent targeting of STAT3 to proteasome-degradation in breast cancer cells (MDA-MB-231, Hs578T, MCF-7, and T47D). We show that blockade of proteasome activity, by MG-132 and bortezomib, or ROS accumulation, by N-acetylcysteine (NAC), restored the level of STAT3 protein. In addition, using chick embryo tumor growth assay, we showed that carnosol significantly and markedly suppressed tumor growth and metastasis of breast cancer xenografts. To the best of our knowledge, this is the first report which shows that carnosol specifically targets signal transducer and activator of transcription 3 (STAT3) for proteasome degradation in breast cancer. Our study further provide evidence that carnosol may represent a promising therapeutic candidate that canmodulate breast cancer growth and metastasis.